Reliability of anthropometric landmarks on body surface for estimating pelvic incidence without lateral X-ray - Ebara, Takeshi; Kamijima, Michihiro; Aoki, Kazuji; Inada, Atsushi; Kimura, Shingo; Uehara, Toru; Yamada, Shota (Environmental and Occupational Health Practice, 2021)
Objectives: Increasing attention has been paid to pelvic incidence (PI) as a potential parameter related to low back pain. However, little knowledge exists regarding potential anthropometric landmarks specialized for the estimation of PI. This study aimed to examine the inter- and intra-examiner reliability of potential anthropometric landmarks applicable to estimate PI. Methods: Twenty healthcare workers were recruited as participants. Three were experienced physiotherapists for more than 5 years in clinical practice. Eight anatomical landmarks were selected: (1) the acromion, (2) the upper edge of the iliac crest, (3) the posterior superior iliac spine (PSIS), (4) the anterior superior iliac spine (ASIS), (5) the upper edge of the greater trochanter, (6) the coccyx, (7) the lateral joint space of the knee, and (8) the lateral malleolus. Photographs of the right-side view of the subjects were used to determine the two-dimensional (x, y) coordinates of the landmarks. Results: Most landmark measurements reached acceptable levels for intra-examiner (ICC1, 0.64 to 0.98) and inter-examiner reliability (ICC3, 0.71 to 0.97). However, as possible anatomical landmarks, the PSIS (ICC1 0.65, ICC3 0.48), acromion (ICC3 0.66), and coccyx (ICC1 0.64) tended to have relatively low ICCs. Conclusions: Our study suggests that potential anthropometric landmarks on the body surface examined on palpation have acceptable intra- and inter-examiner reliability; however, identifying the acromion, PSIS, and coccyx as anatomical landmarks using the measurement method in this study remain difficult to be considered reliable.